COMPARATIVE MEDICINE REVIEW OF IMMUNE-MEDIATED NEPHROTIC SYNDROME DUE TO BABESIA INFECTION. - Nicola Wannenburg (Student’s Journal of Health Research Africa, 2024)
Awareness regarding the need for One Health is steadily increasing. This is largely due to the zoonotic element of many diseases. The past two decades have also shown increased support for translational and comparative medicine where animals with naturally occurring non-communicable diseases as well as zoonotic diseases that are also observed in humans are studied to advance both veterinary and human medicine. Understanding renal disease progression and possible means of diagnosis as well as treatment to prevent end-stage renal failure is critical to both human and veterinary medicine. Nephrotic syndrome is of particular interest due to its challenging progression and associated proteinuria/albuminuria, which if left untreated may rapidly lead to end-stage kidney failure or death by related physical complications. Nephrotic syndrome may be caused by an immune cascade from parasitic infections such as Babesia infection. Babesia is progressively becoming a global zoonotic concern for humans, including associated immune-mediated renal disease. Due to the large number of companion and feral animals infected with Babesia, the disease process and associated complications, such as nephrotic syndrome and acute liver failure are more fully understood in these species. This review aims to explore immune-mediated nephrotic syndrome due to Babesia infection in companion animals and developments in diagnosis and treatment as well as the applicability to human medicine. Advancement in urine analysis for glomerular and tubule injury biomarkers as well as the detection of immunoglobulins in urine shows promise as a less invasive means of diagnosis than renal biopsy in small and very ill patients. Further research on felines with immune-mediated nephrotic syndrome may deliver valuable information for both veterinary and human medicine and may also provide transferable insights to large human and feline populations with immunodeficiency.